Psychological Effects of Visual and Animated Media on Reading Fluency in Early Elementary Students - Axvelgion Revo; Tuti Rahmi (Da'wa Faculty of Islamic State University Salatiga, 2026)
This study examines the psychological effects of visual images and animated videos on reading fluency among first-grade elementary school students, focusing on cognitive processing. Reading fluency involves not only academic ability but also attention, information processing, and memory integration. The study used an experimental design with the non-parametric Kruskal-Wallis H test to compare three groups: visual image media (Group A), animated video media (Group B), and a control group (Group C). Thirty first-grade students were randomly assigned to the groups. Reading fluency was measured using standardized pretest and posttest assessments. The findings revealed that both visual images and animated videos significantly improved reading fluency compared to the control group (p < 0.001). Group A showed the greatest improvement, followed by Group B, while the control group demonstrated minimal change. Psychologically, visual images may support more effective cognitive processing by reducing cognitive load and strengthening dual coding mechanisms, which enhance reading performance. Animated videos, although engaging, may increase cognitive demands at early developmental stages. These findings indicate that the effectiveness of instructional media is closely related to children’s cognitive development and information processing capacity in supporting early reading fluency.